2015
DOI: 10.1186/s13000-015-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of postoperative hepatic granuloma presumptively caused by surgical staples/clipping materials

Abstract: A 66-year-old man with postsigmoidectomy status for colon cancer received laparoscopic partial hepatectomy due to a hepatic mass with employing titanium clips were for a vascular clamp. Histological examination showed liver metastasis from sigmoid colon cancer. Twenty-nine months after the partial hepatectomy, a mass developed on the stump at the hepatic resection. Laparoscopic left lateral segmentectomy was conducted under suspicion of cancer recurrence and an automatic titanium stapling device was used. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…As a result, artifacts owing to its high X–ray absorption coefficient can interfere with the examination of patients using computed tomography and lead to misdiagnoses in the area around the staples for the rest of their lives. Moreover, some studies have reported the adverse effects of Ti alloy staples, including allergic and foreign–body reactions and adhesion 58 . To overcome these disadvantages, biodegradable surgical staples are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, artifacts owing to its high X–ray absorption coefficient can interfere with the examination of patients using computed tomography and lead to misdiagnoses in the area around the staples for the rest of their lives. Moreover, some studies have reported the adverse effects of Ti alloy staples, including allergic and foreign–body reactions and adhesion 58 . To overcome these disadvantages, biodegradable surgical staples are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Granulomas might develop adjacent to surgical areas or scars, and the presence of metal particles originating from components of the instruments used during the surgery or from the implants or prostheses themselves is well documented. [12][13][14][15][16][17]34,35 Therefore, particles or debris of all sizes, which are generally pigmented and birefringent or not under polarizing light microscopes, are regularly observed by on-duty pathologists. 35 Some assumptions can be made about the presence of these foreign metals.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of foreign material in tissues after surgery was also investigated. This aspect has been largely documented, [12][13][14][15][16][17] and several exogenous substances, such as particles or debris, may originate from the release of components of surgical instruments, sutures, staples, implants, among other sources.…”
Section: Exogenous Particles After Surgerymentioning
confidence: 99%
“…We have read the case report of Nihon-Yanagi et al [ 1 ] with great interest. The patient they described developed hepatic granuloma(HG) two times and the granulomatous lesion was surrounding metal staples/clips suggesting that the granuloma was due to surgical/staples/clips.…”
Section: Letters To the Editormentioning
confidence: 99%